Pemberian Rebusan Daun Kelor untuk Menurunkan Tekanan Darah - Kadriah Kika; Sudarman; Haeril Amir; Andi Yuliana (Pusat Kajian dan Pengelola Jurnal FKM UMI, 2026)
Moringa oleifera decoction is a non-pharmacological therapy that plays an important role in controlling LDL in the blood which is the forerunner of hypertension. This study aims to determine the effect of giving moringa leaf decoction to reducing blood pressure in the working area of the Bontomarannu Public Health Center 2023. In this study the method used was quantitative research with a quasy experimental design pre and posttest non-equivalent control group. 55 people participated in this research. A sample of 48 people was determined by purposive random sampling which was divided into 24 people from the control and intervention groups. The statistic test used an independent t-test to determine the effect of moringa oleifera decoction on lowering blood pressure. The results showed that there were significant changes in systolic blood pressure p=0.01 and diastolic blood pressure p=0.01. The conclusion of this research is that giving Moringa oleifera lowers blood pressure. Therefore, through this research, people can apply this non-pharmacological therapy as a traditional treatment in reducing blood pressure.